Budgeting For The Holidays - Donna Davis; Josephine Turner (EDIS)
FAR-9000, a 2-page transcript of the radio broadcast by Donna Davis and Josephine Turner, provides tips for keeping holiday spending within budget. Includes links to sounds files of the radio broadcast. Published by the UF Department of Family Youth and Community Sciences, June 2006.